From the seven days - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 1993)
AUS DEN SIEBEN TAGEN / FROM THE SEVEN DAYS Intuitive Music (15 recordings on 7 CDs)Edition with booklet in English (124 pages).